Etiology and bases of tissue hardening in heat-treated papaya (Carica papaya L.) fruits - Bacay-Roldan, Marissa; Serrano, Edralina P. (2005)
The development and mechanism involved in the formation of tissue hardening in heat-treated fruits of 'Solo' papaya (Carica papaya L.) were investigated. Fruits were subjected to hot water treatment (49 C for 120 min) to induce the development of hardened tissues. Tissue hardening was more prominent in the inner tissues (-1.5- to 2.0-cm diameter) surrounding the seed cavity. It was accompanied by a decrease in total sugars and ion leakage. 1-aminocyclopropane- 1-carboxylic acid (ACC) oxidase activity was inhibited in tissue-hardened fruits, resulting in the accumulation of ACC but with a reduction in ethylene production. The suppressed thylene production inhibited or reduced other ripening-related processes, ultimately causing a 2-d delay in color change of the peel, tissue hardening or reduced firmness and a concomitant decrease in pulp color development. On the other hand, the respiration process was not significantly altered, indicating that O2 and CO2 levels were not involved in tissue hardening. Polygalacturonase (PG) and xylanase decreased since these are heat-sensitive, thus, dissolution of the middle lamella and destruction of the cell wall were inhibited, and membrane integrity of hardened tissues was maintained as shown by a reduced ion leakage and viscosity as the fruits ripened. Xylanase was involved in the softening of papaya fruit up to peel color index 3 stage, while PG continued to play an important role in the degradation of cell wall components after xylanase activity declined.
Keywords: Papaya; Plant cells & tissues